Ensuring Cash-Intensive Efficiency in The Village: Meta Frontier Analysis - Abdulkadir, Amanah; Afriana, Wendra; Azis, Harry (Universitas Airlangga, 2021)
Inequality, poverty, and unemployment in villages are still problems that have not been adequately resolved to date. Starting to allocate village funds in 2015 and Cash For Work (CFW) in 2018, it hopes this would accelerate these problems. This study uses a meta frontier analysis. This study found three factors that significantly affected inefficiency: the variable number of villages that had not budgeted for CFW â‰¥30%, the number of villages that had not reported CFW, and the CFW process status â‰¥ 30%. This study proposes three policy recommendations, including the 30 percent minimum working day (HOK) limit that is no longer a benchmark and gives villages the freedom to use the Village Fund using the self-management method. Second, the Government should synergize data on poverty reduction programs and unemployment between ministries or institutions. Third, the Village Government must prioritize the development of village potential while still empowering marginalized communities. Keywords: Efficiency, Cash Intensive WorkJEL: D72, H7